(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the relationship between harmful oral habits and child behavior. Methodology: An integrative review of the literature was developed based on the PRISMA model and based on the guiding question: - Is there scientific evidence that there is a relationship between harmful oral habits and child behavior? There was an exploratory search on the virtual portals of PubMed, VHL and SciELO, adopting the health descriptors or MeSH terms: “children”, harmful oral habits”, and “child behavior”, in the versions in Portuguese, English and in Spanish, with no time limit regarding the time of publication. The Boolean operators “AND”, “OR” and “NOT” were adopted, in addition to the inclusion and exclusion criteria, in the study selection process. From 114 records, four eligible works were included. Conclusion: although the importance of behavioral and psychological aspects in the prevalence of harmful oral habits among children is emphasized, there are still gaps in strong scientific evidence on the topic. Depression and lower levels of resilience in children were associated with the presence of harmful oral habits, as well as punitive attitudes and an increase in their prevalence. There has been controversy about the relationship between anxiety and the presence of harmful oral habits in children.